Analisis Harapan Dan Kepercayaan Pelanggan Terhadap Minat Beli Online Pada Saat Pandemi Covid-19 - Vira Ristani; Herry Nurdin (Economy Deposit Journal (E-DJ), 2021)
This research was conducted to determine the extent of the analysis of custumer expectations and trus in custumer expectations and trus in customer buying interest online at time of covid-19. This type of research is associative research. The population is all people who use online purchasing facilities. The sampling technique was convenience sampling. In this study, the number of sampling used was 50 respondents. The type of data. The data source used is primary data. Data collection techniques are observation, interviews, questionnaires and literature study related to this research variable. Data analysis techniques are using the validity test, reliability rest, classical assumptions (normality test, multicollinearity test, heteroscedasticity test, outocorrelation rest), multiple linier regression analysis, correlation coefficient analysis, determination test, t tes, f test, expectation does not have a significant effech on purchase intention, while trust has a positive and significant effech on purchase intention.